Highly stable graphene-oxide-based membranes with superior permeability - Khalid Hussain Thebo (Nature Portfolio, 2018)
Graphene oxide membranes show great potential for water filtering, but improving their performance and stability remains difficult. Here, the authors use theanine amino acid and tannic acid to reduce and cross-link graphene oxide membranes with remarkably high permeability and stability in aqueous solution.